Exocytosis reconstituted from the sea urchin egg is unaffected by calcium pretreatment of granules and plasma membrane. Issue 4 (August 1988) - Whalley, Tim; Whitaker, Michael
Abstract : Micromolar calcium ion concentrations stimulate exocytosis in a reconstituted system made by recombining in the plasma membrane and cortical secretory granules of the sea urchin egg. The isolated cortical granules are unaffected by calcium concentrations up to 1 mM, nor do granule aggregates undergo any mutual fusion at this concentration. Both isolated plasma membrane and cortical granules can be pretreated with 1 mM Ca before reconstitution without affecting the subsequent exocytosis of the reconstituted system in response to micromolar calcium concentrations. On reconstitution, aggregated cortical granules will fuse with one another in response to micromolar calcium provided that one of their number is in contact with the plasma membrane. If exocytosis involves the generation of lipid fusogens, then these results suggest that the calcium-stimulated production of a fusogen can occur only when contiguity exists between cortical granules and plasma membrane. They also suggest that a substance involved in exocytosis can diffuse and cause piggy-back fusion of secretory granules that are in contact with the plasma membrane. Our results are also consistent with a scheme in which calcium ions cause a reversible, allosteric activation of an exocytotic protein.